The Role of Thyroglobulin in Preoperative and Postoperative Evaluation of Patients With Differentiated Thyroid Cancer - Li, Sha; Ren, Chutong; Gong, Yi; Ye, Fei; Tang, Yulong; Xu, Jiangyue; Guo, Can; Huang, Jiangsheng (Frontiers in Endocrinology, 2022)
Thyroglobulin (Tg) is secreted by thyroid follicular cells and stored in the thyroid follicular lumen as a component of thyroid hormone. It is known that both benign and well-differentiated malignant thyroid tissue can secret Tg. In recent years, growing shreds of evidence have shown that Tg plays an important role in the diagnosis and metastasis of preoperative differentiated thyroid carcinoma (DTC). The levels of Tg, whether in the serum or in a fine-needle aspiration washout fluid, are usually viewed as an excellent indicator in the monitoring of postoperative DTC, including the guidance and evaluation of radioactive iodine ablation. Nevertheless, some factors limit the application of Tg, such as the method used to measure Tg and the presence of Tg-antibodies. This review aimed to summarize the role of Tg in the preoperative and postoperative evaluation of patients with DTC, and the factors influencing Tg. This review could provide a reference for a more accurate application of Tg in patients with DTC.